Pentapeptide PYRAE triggers ER stress-mediated apoptosis of breast cancer cells in mice by targeting RHBDF1-BiP interaction - Ryu SungJu; Long Hui; Zheng Xin-ling; Song Yuan-yuan; Wang Yan; Zhou Yu-jie; Quan Xiao-jing; Li Lu-yuan; Zhang Zhi-song (Acta Pharmacologica Sinica, 2024)
Reinforced cellular responses to endoplasmic reticulum (ER) stress are caused by a variety of pathological conditions including cancers. Human rhomboid family-1 protein (RHBDF1), a multiple transmembrane protein located mainly on the ER, has been shown to promote cancer development, while the binding immunoglobulin protein (BiP) is a key regulator of cellular unfolded protein response (UPR) for the maintenance of ER protein homeostasis. In this study, we investigated the role of RHBDF1 in maintaining ER protein homeostasis in breast cancer cells. We showed that deleting or silencing RHBDF1 in breast cancer cell lines MCF-7 and MDA-MB-231 caused marked aggregation of unfolded proteins in proximity to the ER. We demonstrated that RHBDF1 directly interacted with BiP, and this interaction had a stabilizing effect on the BiP protein. Based on the primary structural motifs of RHBDF1 involved in BiP binding, we found a pentapeptide (PE5) targeted BiP and inhibited BiP ATPase activity. SPR assay revealed a binding affinity of PE5 toward BiP (Kd = 57.7 μM). PE5 (50, 100, 200 μM) dose-dependently promoted ER protein aggregation and ER stress-mediated cell apoptosis in MCF-7 and MDA-MB-231 cells. In mouse 4T1 breast cancer xenograft model, injection of PE5 (10 mg/kg, s.c., every 2 days for 2 weeks) significantly inhibited the tumor growth with markedly increased ER stress and apoptosis-related proteins in tumor tissues. Our results suggest that the ability of RHBDF1 to maintain BiP protein stability is critical to ER protein homeostasis in breast cancer cells, and that the pentapeptide PE5 may serve as a scaffold for the development of a new class of anti-BiP inhibitors.